Treating Calf and Pedal Vessel Disease: The Extremes of Intervention - Manzi, Marco; Palena, Luis M. (Seminars in Interventional Radiology, 2014)
Recent developments in catheter, balloon, and guidewire technology have increased the scope for endovascular treatments in the management of complex and challenging disease in the calf and foot. The antegrade femoral approach remains the starting point for most interventions, but there is a growing role for procedures performed from unconventional access such as the pedal arteries. This article reviews the indications for intervention, atypical access, and the choice of equipment for these extreme interventions.
Keywords: below-the-knee; below-the-ankle; angiosome; transpedal; pedal–plantar loop; interventional radiology